2019
DOI: 10.1007/s40519-019-00692-x
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behaviours and correlates in yoga practitioners: a systematic review

Abstract: Purpose: Yoga has been increasingly used as a complementary therapy for eating disorders. However, it is still not clear whether yoga is effective in the prevention and treatment of eating disorders, as some studies suggest that yoga practitioners show elevated levels of disordered eating behaviours. The goal of this systematic review is, thus, to analyse the occurrence of disordered eating behaviours and correlates in yoga practitioners.Method: PRISMA guidelines for systematic reviews were used. Search was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
2
9
0
2
Order By: Relevance
“…Furthermore, some longitudinal and intervention studies have suggested that yoga may be effective in improving body image and disordered eating behaviors (Halliwell et al, 2019; Neumark‐Sztainer, MacLehose, et al, 2018; Ariel‐Donges et al, 2019; Cox et al, 2017; McIver, O'Halloran, & McGartland, 2009; Brennan et al, 2020). Although findings do not consistently show the benefits of yoga (Domingues & Carmo, 2019; Ostermann et al, 2019), we are not aware of research findings showing that yoga can be harmful in terms of worsening these outcomes.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, some longitudinal and intervention studies have suggested that yoga may be effective in improving body image and disordered eating behaviors (Halliwell et al, 2019; Neumark‐Sztainer, MacLehose, et al, 2018; Ariel‐Donges et al, 2019; Cox et al, 2017; McIver, O'Halloran, & McGartland, 2009; Brennan et al, 2020). Although findings do not consistently show the benefits of yoga (Domingues & Carmo, 2019; Ostermann et al, 2019), we are not aware of research findings showing that yoga can be harmful in terms of worsening these outcomes.…”
Section: Discussionmentioning
confidence: 73%
“…The practice of yoga has been shown to be associated with a number of positive physical and emotional health outcomes (25)(26)(27)(28)(29). Reviews of research examining the relationships between practicing yoga and body image, disordered eating behaviors, and eating disorders, suggest that yoga may be bene cial, although associations tend to be modest and are not always consistent across studies (16,(30)(31)(32)(33). For example, in a mixed-methods pilot study examining a yoga-based intervention conducted within an eating disorders treatment center, participants described many positive changes to their body image as a result of their yoga practice (34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dennoch ist zu beachten, dass Yoga in der Therapie der AN zu unerwünschten Nebenwirkungen führen könnte [23]. So könnte der Vergleich mit anderen, die innere kritische Stimme, aber auch eine zu häufige Yoga-Praxis oder zu starke Selbstdisziplin die Essstörungsymptomatik negativ beeinflussen [14,24,25].…”
Section: Introductionunclassified
“…The practice of yoga has been shown to be associated with a number of positive physical and emotional health outcomes (25)(26)(27)(28)(29). Reviews of research examining the relationships between practicing yoga and body image, disordered eating behaviors, and eating disorders, suggest that yoga may be bene cial, although associations tend to be modest and are not always consistent across studies (16,(30)(31)(32)(33). For example, in a mixed-methods pilot study examining a yoga-based intervention conducted within an eating disorders treatment center, participants described many positive changes to their body image as a result of their yoga practice (34).…”
Section: Introductionmentioning
confidence: 99%